Gender decision dilemma of Disorders of Sex Development (Khunsa) in Islamic Law with medical approach - Susilo, Edi; Zahro, Ahmad; Santoso, Budi; Faradz, Sultana MH (Penerbit Universiti Kebangsaan Malaysia, 2022)
Disorder of Sex Development defined as congenital conditions in which the development of chromosomal, gonadal, or anatomic sex is atypical. In Islam, gender decision of khunsa is difficult since it still relies on the traditional approach of observing how people urinate and observing the physical features that emerge, whereas gender identity must be determined early because it affects every day worship activities. The goal of this research is to use a medical method to examine the renewal of khunsa gender determination in Islam. The descriptive qualitative analysis method is used in this study. The findings of this study suggest that in Islam, determining khunsa gender through a medical approach is warranty. In Islam, the importance of gender identity is particularly significant in issues of worship, such as congregational prayers, inheritance, aurat limitations, and marriage. Understanding and adjustment of medical diagnosis issues, community culture, and religious law need to be synchronized to improve the quality of life for people with gender ambiguity that do not deviate from religious principles and can be accepted in society without discrimination. To the best of our knowledge this is the first study of combine Islamic law and modern medicine.